2021
DOI: 10.1128/aem.02597-20
|View full text |Cite
|
Sign up to set email alerts
|

Method for Measuring Phenotypic Colistin Resistance in Escherichia coli Populations from Chicken Flocks

Abstract: Colistin is extensively used in animal production in many low- and middle-income countries. There is a need to develop methodologies to benchmark and monitor changes in resistance among mixed commensal bacterial populations in farms. We aimed to evaluate the performance of a broth microdilution method based on culturing a pooled Escherichia coli suspension (30-50 organisms) obtained from each sample. To confirm the biological basis and sensitivity of the method, we cultured 16 combinations of one colistin-susc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Here, the collection of detailed and reliable AMU data on a weekly basis allows us to account for the dynamics of the effect of AMU on AMR. We find that our measure of colistin resistance is associated with the use of antimicrobials during the 1.73 weeks preceding the sample collection, similarly to (Nhung et al., 2021 ). The reason may be that AMU selects for colistin resistant E. coli strains that were already present at low level or that were introduced to the farm.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Here, the collection of detailed and reliable AMU data on a weekly basis allows us to account for the dynamics of the effect of AMU on AMR. We find that our measure of colistin resistance is associated with the use of antimicrobials during the 1.73 weeks preceding the sample collection, similarly to (Nhung et al., 2021 ). The reason may be that AMU selects for colistin resistant E. coli strains that were already present at low level or that were introduced to the farm.…”
Section: Discussionsupporting
confidence: 77%
“…For each sample, this measure was repeated twice and averaged. The method, validated by Nhung et al (2021), aims to obtain an aggregated estimate of colistin resistance among a representative sample of the whole E. coli population circulating in the guts of all the chickens of the flock of each farm and at each time point.…”
Section: Estimation Of Colistin Resistance In Samplesmentioning
confidence: 99%
“…13–16 Studies in the Mekong Delta region have documented an increase in colistin and gentamicin resistance in Escherichia coli from two-month-old chickens compared with day-old chicks. 14 , 15 In contrast, decreases in prevalence of resistance to tetracyclines and sulphonamides have been reported in E. coli isolated from day-old chicks to maturity in laying hens in Europe. 16 Using longitudinal data from chicken flocks in the Mekong Delta (Vietnam), a modelling study on colistin resistance indicated that AMU in the early stage of production or introduction from hatcheries is far less determinant than importation from the environment and use in latter stages.…”
Section: Introductionmentioning
confidence: 99%